Validation of the Sun Exposure and Protection Index (SEPI) in Greek: An Instrument for Measuring Children’s Sun Protection Propensity - Theodosi, Sotiroula; Nicolaidou, Iolie (My University, 2023)
Skin cancer, the most common type of cancer worldwide, has been linked to overexposure to ultraviolet radiation (UVR) without protection. As skin cancer is a preventable type of cancer, there is a pressing need to adopt health-promoting behaviors early in life. The Sun Exposure and Protection Index (SEPI) is an instrument for evaluating adults’ sun exposure habits and the propensity to increase sun protection with widely accepted validity and reliability in Swedish, English, and German. The present study aims to validate SEPI with children in Greek. Data was collected from 127 primary school students in Cyprus who completed the instrument twice within two weeks. Internal consistency calculated by Cronbach’s alpha was 0.69 for all 13 items included in SEPI. A statistically significant (p < 0.01) strong and positive correlation coefficient (Pearson’s r = 0.63) was measured between the total scores for parts 1 and 2. Test–retest stability was high and significant (ρ > 0.5, p < 0.01) for all items but one. In conclusion, the Greek version of SEPI demonstrates reasonable internal consistency, as Cronbach’s alpha is at a relatively acceptable level. It can be used for evaluating prevention interventions assessing sun exposure habits, and the propensity to increase sun protection among primary school students.
Keywords: validity; reliability; ultraviolet radiation (UVR); children; UVR protection attitudes; habits; behaviors; questionnaire